KAJIAN “ADAB MEMAKAI TANJAK” DI FAKULTAS ILMU BUDAYA UNIVERSITAS LANCANG KUNING PEKANBARU - Juswandi, Juswandi; Hermansyah, Hermansyah; Amanan, Amanan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
This research is a study of "Adab Using Tanjak". This research was conducted at the Faculty of Cultural Sciences and the Faculty of Law at the Lancang Kuning University Pekanbaru. This study aims to analyze so that it can be understood as well as teaching material for Malay culture courses. With the expectation when teaching Malay cultural subjects it is not wrong to teach students.